Meat from young goats raised in argan tree forest (Morocco): emerging product to valorise - El Aïch A.; Morand-Fehr P.; Bas P.; Araba A.; Bourbouze A. (Mediterranean livestock production: uncertainties and opportunities, 2008)
During the past few years, the ecology of Argan tree forest (800 000 ha in SW Morocco) and the argan oil have been studied extensively. Goats, particularly the rearing of yearling males, constitute an important component of the argan farming system. Young goats are reared outdoors on the argan rangelands without conventional concentrate supplies, except some argan by-products. Recent experiments supported by the PRAD programme (PRAD 0011) showed that in comparison with an indoors feeding (usual system in Morocco) the meat produced by argan tree grazing, supplemented or not, presents lower lipids and cholesterol contents, higher proportions of n-6 and n-3 (PUFA) and a lower n-6/n-3 PUFA ratio, which results in beneficial characteristics for human health. The meat of these goats is appreciated mainly by local consumers: this was confirmed by the sensory panels during the experiments. But, in Morocco, the frequency of cardio-vascular diseases is progressing and consumers are tending to coming back to traditional products. Kids raised in the Argan area present the characteristics to cover the demand of Moroccan consumers in the future. Due to the limited number of carcasses produced, this meat could be only a niche product. For developing its market, it would be better to organize the production and trade chain by setting up goat farmers groups and an organization involving all partners such as slaughterers and butchers.
2. Seminar of the Scientific-Professional Network on Mediterranean Livestock Farming (RME), 2006/05/18-20, Zaragoza, (Spain)